Infiltration of Blood-Derived Macrophages Contributes to the Development of Diabetic Neuropathy - Jing-Jing Sun; Lin Tang; Xiao-Pei Zhao; Jun-Mei Xu; Yang Xiao; Hui Li (Journal of Immunology Research)
Background and Objective. Diabetic neuropathic pain (DNP) is a common complication associated with diabetes. Currently, its underlying pathomechanism remains unknown. Studies have revealed that the recruitment of blood monocyte-derived macrophages (MDMs) to the spinal cord plays a pivotal role in different models of central nervous system injury. Therefore, the present study aimed at exploring the infiltration and function of MDMs in DNP using a mice model. Methods. Diabetes was induced using streptozotocin in male A/J mice. Mechanical withdrawal thresholds were measured weekly to characterize neuropathy phenotype. Quantitative analysis of CD11b was performed and visualized by immunofluorescence. Spinal cord cells were isolated from myelin and debris by Percoll gradient. Flow cytometry was used to label CD11b and CD45 antibodies to differentiate MDMs (CD45highCD11b+) from resident microglia (CD45lowCD11b+). Mice were injected with clodronate liposomes to investigate the role of MDMs in DNP. The successful depletion of monocytes was determined by flow cytometry. Results. The DNP mice model was successfully established. Compared with nondiabetic mice, diabetic mice displayed a markedly higher level of CD11b immunofluorescence in the spinal cord. The number of CD11b-positive microglia/macrophages gradually increased over the 28 days of testing after STZ injection, and a significant increase was observed on Day 14 (P<0.01) and 28 (P<0.01). Further analysis by flow cytometry showed that the infiltration of peripheral macrophages began to increase in 2 weeks (P<0.001) and reached a maximum at 4 weeks (P<0.001) post-STZ injection compared to the control. The depletion of MDMs by clodronate liposomes alleviated diabetes-induced tactile allodynia (P<0.05) and reduced the infiltration of MDMs (P<0.001) as well as the expression of IL-1β and TNF-α in the spinal cord (P<0.05). Conclusions. The infiltration of blood MDMs in the spinal cord may promote the development of painful neuropathy in diabetes.